The Impact of COVID-19 on Demand and Lending Behavior in Prosocial P2P Lending - Christopher Priberny (Credit and Capital Markets – Kredit und Kapital, 2023)
I derive two innovative metrics, capturing the demand and the excess demand for prosocial P2P loans in the US. The measures are based on a data set comprising prosocial P2P loan applications obtained from the US P2P lending platform Kiva for the period of November 2011 to December 2022. Furthermore, I analyze how both indices are influenced by the COVID-19 pandemic. Interestingly, the measures for the current pandemic development show a negative impact on demand while the COVID-19 reproduction rate shows a positive relation, indicating a pro-active behavior of borrowers. On the other side, socially motivated lenders seem to be less generous in providing interest-free loans in times of a worsening pandemic. As it turns out, the risk-free interest level positively impacts demand and excess demand for prosocial lending on Kiva even though the loans were granted without any interest.
Keywords: G20; G21; G41; 330; KIVA; prosocial P2P lending; demand; lending behavior; COVID-19